IMPLEMENTATION SHA 512 BIT ON ROUTING URL (Jurnal Ipteks Terapan, 2023)
This research aims for implementation SHA512 on routing URLs in system information can increase security And integrity data. With apply algorithm hashing SHA512,user data sent via routing URLs is effectively encrypted, thereby reducing the risk of data manipulation and hacking. These results are corroborated by Analysis statistics Which done involve collection data from system information before And after implementation SHA512 on routing URLs. Data Which collected covers attack Which detected, effort hack, successful unauthorized access, and data manipulation. this data then analyzed using relevant statistical methods to identify change Which significant in security system. Study This give contributionimportant For strengthen security system information And protect integrity data